Endpoint Estimates for an Oscillatory Multiplier Associated with Wave Equations on the Torus (Journal of Mathematical Study, 2024)
In this paper, we establish the endpoint estimate for an oscillatory multiplierassociated with wave equations on the torus, which extends the results of Fan andSun. In addition, we obtain a more general result for sublinear operators on compactmeasure spaces.